Survei Fundamental Psikomotor Siswa Kelas V dan VI SD Islam Sukorejo Kec. Sukorejo Kota Blitar - Huda, Dhimas Miftachul; Setiawan, Irwan; Firdaus, Mokhammad (YLPK Mahardhika, 2024)
Lack of physical activity causes a decrease in children's fundamental movement abilities. The aim of this research was to determine physical activity on the Psychomotor Fundamentals of Class V and VI Elementary School Students. This research uses a descriptive quantitative approach. The place where this research was carried out was at Sukorejo Islamic Elementary School, Kec. Sukorejo, Blitar City. The population in this study were 57 grade V and VI elementary school students. The sampling technique used total sampling. The instrument used in this research was the Test of Gross Motor Skill-second edition (TGMD-2). Data collection carries out tests. The data analysis technique uses quantitative descriptive with percentages. The results showed that in class 5 there were 5 male students who received the average category, 1 male student received the below average category, 7 male students received the low category, 1 male student received the very low category, 5 female students got the average category, 1 female student got the below average category, 5 female students got the low category, while in class 6 there were 4 male students who got the above average category, 10 male students got the category on average, 3 male students got the below average category, 1 male student got the low category, 8 female students got the average category, 5 female students got the below average category, 1 female student got the low category.